Effect of Candesartan, Atenolol and Amlodipine on Oxidative Stress in Kerbala Patients with Hypertension - Mohammed Talat Abbas (Journal of Global Pharma Technology, 2018)
Hypertension is a heterozygous disorder in which patients can be stable according to pathophysiological characteristics that have a direct effect on the effectiveness of specifically targeted antihypertensive drugs on detecting recoverable forms of hypertension and the risks of cardiovascular complications. This study was performed to compare the effect of anti-hypertension drug with etenolol, amlodipine and candesartan on oxidative stress in kerbala patients with primary hypertension. A total of 60 hypertensive patients (20 patients with etenolol, 20 patients on amlodipine and 20 candersarten) and 20 health components in the study. In conclusions Treatment with etenolol, amlodipine and candesartan reduces SBP, DBP, and MDA and improves the antioxidant system (SOD, CAT).Keywords: Hypertension, Etenolol, Amlodipine, candesartan, Oxidative stress.